The implications of the COVID-19 pandemic on South African food security: A paradigmatic turn for building back better - Manduna, Kennedy (The International Journal of Sociology of Agriculture and Food, 2023)
This paper explores the impact of the COVID-19 pandemic on South Africa’s food security, as there is a yawning scholarly gap in this nascent area. In 2020, about 23.6% of South Africans experienced moderate to severe food insecurity, while 14.9% experienced severe food insecurity. Therefore, by applying the United Nations’ Food Insecurity Experience Scale (FIES), this paper classifies victims of food insecurity into two groups: those who experienced moderate to severe food insecurity, and those who experienced severe food insecurity. To put the impact of this insecurity into perspective, I simultaneously present and discuss the country’s food insecurity pre-pandemic and during the pandemic. Therefore, this desktop-based paper answers the following research question: How has the COVID-19 pandemic worsened the food insecurity crisis in South Africa, and what practical and resilient measures should the South African government adopt and implement to ensure sustainable food security? Findings have established that the pandemic and the measures implemented to contain it exacerbated pre-existing economic vulnerabilities and exposure among poor South Africans, particularly Black Africans. The pandemic-triggered hunger and food insecurity was thus racialised, gendered and regionalised, pointing to the structural inequalities that have characterised South Africa since colonialism and apartheid to the present day. Therefore, for sustainable and resilient food security and sovereignty, this paper recommends that Africa in general and South Africa in particular take a paradigmatic turn by designing an effective food insecurity crisis contingency plan. Doing this requires implementing a ‘Do-it-Yourself Africa’ approach in food production and distribution.